Meningkatkan Nilai Tambah Produk Minuman Kekinian Dengan Zat Warna Alami dari Bunga Telang dan Kayu Secang di DesaLingsuh, Rajabasa, Bandar Lampung - Utami, Heri; Febriningrum, Panca Nugrahini; Azhar; Rustamaji, Heri (Nemui Nyimah, 2024)
Most food or drink products consumed by the public have coloring added with the aim of making the product more appetizing and attractive. This service collaborates with partners consisting of PKK women and housewives in Desa Lingsuh, Rajabasa, Bandar Lampung. Partners still have limited knowledge about dyes in food or beverage products. Both synthetic dyes and natural dyes used in food and beverage products are still not known in detail. Some of the partners have beverage sales businesses, in which case they do not use natural dyes as coloring agents in their beverage products. The Service Team provides solutions by providing knowledge transfer about natural dyes that can be used in their beverage products and the added value of using natural dyes, as well as how to make them and use them in the beverage products they sell. Making contemporary drinks using natural dyes can be done using simple methods and raw materials that are easy to obtain and cheap. This activity is expected to have an impact on the selling value of partner beverage products and also benefit consumers of partner products, especially in the use of natural dyes which are beneficial for health. The programs implemented in this service include education about the benefits of natural dyes in drinks, practice of making natural dyes from telang flowers and secang wood, as well as practicing making contemporary drinks. With this service program, partners gain new knowledge that is very useful during training and practice and can be used in the products they sell.